An elusive common : land, politics, and agrarian rurality in a Moroccan oasis - Rignall, Karen E., 1970- (Cornell series on land., 2021)
"This book documents how small farmers and other residents in Morocco's southeastern oases engage with global markets to invest new resources and meaning in their rural communities. They use their global engagements to challenge their historical oppression and reinvigorate customary land tenure and social arrangements"--